The shadow of your smile [compact disc, unabridged] : a novel - Clark, Mary Higgins (Audioworks/Simon & Schuster Audio, 2010)
At age eighty-two and in failing health, Olivia Morrow must decide whether she will expose a long-held family secret and reveal that her cousin, Catherine, gave birth to a son at age seventeen and gave him up for adoption before entering a convent. Now deceased, Sister Catherine is being considered for beatification by the Catholic Church. Catherine' s granddaughter Monica has no idea that her grandfather was the famous doctor Alex Gannon, and Alex's greedy nephews Greg and Peter Gannon will stop at nothing to keep Monica from learning that she is the rightful heir to the Gannon family fortune.